Chronic mucocutaneous candidiasis due to signal transducer and activator of transcription 1 mutation in a Saudi patient: a case report (Dermatology Reports, 2024)
Chronic mucocutaneous candidiasis (CMC) is a primary immunodeficiency condition caused by a genetic abnormality that increases the risk of recurrent and persistent skin, nail, and mucous membrane infections with Candida species, typically Candida albicans. Signal transducer and activator of transcription 1 (STAT1) gene mutation is a genetic trigger that causes CMC, which increases the risk of infections, multisystem disorders, and cancer susceptibility. We describe the first case of a Saudi female patient with clinical features of CMC with an underlying (STAT1) gene mutation.